Correlation of body compositions and bone mineral density in postmenopausal women with different body mass index - Ge, Song; Li, Min; Bao, Xiaoxue; Wu, Gege; Liu, Mengcong; Zhang, Wei; Li, Yukun; Wang, Yan (Frontiers in Endocrinology, 2025)
BackgroundThe association between obesity and bone mineral density (BMD) is controversial. Body composition parameters have been found to be strongly correlated with BMD. Body mass index(BMI)cannot distinguish between muscle and adipose tissue. The objective of this study was to evaluate the association of body composition with BMD in postmenopausal women with different BMI.Methods356 postmenopausal women were divided into three groups(normal weight, overweight and obesity)according to BMI. BMD and body composition components were obtained by Dual-energy X-ray Absorptiometry. The collected data served as the training set for model development, while datasets from the NHANES database were utilized as a validation set to assess model performance. Multivariable linear regression models evaluated associations between parameters of body composition and BMD in different BMI participants.ResultsIn univariate analysis, BMI, total fat mass, soft lean mass (SLM), appendicular skeletal muscle mass, relative skeletal muscle index (RSMI) were positively correlated with BMD at all sites (r = 0.181–0.388, all P < 0.01).In normal weight subjects, multivariate regression models consistently revealed positive associations of SLM and android-to-gynoid ratio (AOI) with BMD across lumbar spine, hip, and femoral neck sites (Model 1: SLM Sβ=0. 260-0. 313, all P<0.001; AOI Sβ=0.224-0. 289, all P<0.05. Model 2: RSMI Sβ=0.182-0.218, all P<0.01; AOI Sβ=0.174-0.235, all P<0.05). Among overweight subjects, AOI showed site-specific correlations with lumbar spine BMD in both models (Model 1 Sβ=0.207; Model 2 Sβ=0.193), while SLM maintained positive associations with all sites (Sβ=0.238-0.246, P<0.01) and RSMI with femoral neck BMD (Sβ=0.196, P<0.05). No significant body composition-BMD correlations were observed in obese subjects. External validation with NHANES database confirmed model robustness, with all significant β coefficients from the validation set falling within the training set’s 95% CIs.ConclusionsThe study demonstrates that the effect of body compositions on BMD varies by BMI classification and site-specific differences in postmenopausal women. Increased abdominal fat may confer a potential benefit for BMD in non-obese women with relative metabolic health. Conversely, optimizing body composition by reducing body fat and increasing muscle mass remains crucial for skeletal health in postmenopausal women.